New records of Lepidoptera (Insecta) in altitudinal grasslands in state of Santa Catarina, Southern Brazil - Mario Arthur Favretto; Emili Bortolon dos Santos (Acta Biológica Catarinense, 2017)
There is a lack of knowledge regarding Lepidoptera species in altitudinal grassland areas, especially in the state of Santa Catarina, in southern Brazil. Here we report some records of Vanessa braziliensis (Moore, 1883) and Urbanus zagorus (Plötz, 1880) in high altitude areas. We have likely registered both the first record of U. zagorus for the state of Santa Catarina and the highest altitudinal record of V. braziliensis in Brazil.